Impact of nanoparticles on transcriptional regulation of catabolic genes of petroleum hydrocarbon‐degrading bacteria in contaminated soil microcosms. (23rd November 2018) - El‐Sayed, Wael S.; Elbahloul, Yasser; Saad, Mohamed E.; Hanafy, Ahmed M.; Hegazi, Abdelrahman H.; ElShafei, Gamal M. S.; Elbadry, Medhat
Abstract : This study was conducted to determine what effects nanoparticles (NPs) like TiO2, ZnO, and Ag may pose on natural attenuation processes of petroleum hydrocarbons in contaminated soils. The solid NPs used were identified using x‐ray diffraction technique and their average size was certified as 18.2, 16.9, and 18.3 nm for Ag‐NPs, ZnO‐NPs, and TiO2 ‐NPs, respectively. NPs in soil microcosms behave differently where it was dissolved as in case of Ag‐NPs, partially dissolved as in ZnO‐NPs or changed into other crystalline phase as in TiO2 ‐NPs. In this investigation, catabolic gene encoding catechol 2, 3 dioxygenase (C23DO) was selected specifically as biomarker for monitoring hydrocarbon biodegradation potential by measuring its transcripts by RT‐qPCR. TiO2 ‐NPs amended microcosms showed almost no change in C23DO expression profile or bacterial community which were dominated by Bacillus sp., Mycobacterium sp., Microbacterium sp., Clostridium sp., beside uncultured bacteria, including uncultured proteobacteria, Thauera sp. and Clostridia . XRD pattern suggested that TiO2 ‐NPs in microcosms were changed into other non‐inhibitory crystalline phase, consequently, showing the maximum degradation profile for most low molecular weight oil fractions and partially for the high molecular weight ones. Increasing ZnO‐NPs concentration in microcosms resulted in a reduction in the expression of C23DO with a concomitant slight deteriorative effect on bacterial populations ending up with elimination of Clostridium sp., Thauera sp., and uncultured proteobacteria. The oil‐degradation efficiency was reduced compared to TiO2 ‐NPs amended microcosms. In microcosms, Ag‐NPs were not detected in the crystalline form but were available in the ionic form that inhibited most bacterial populations and resulted in a limited degradation profile of oil, specifically the low molecular weight fractions. Ag‐NPs amended microcosms showed a significant reduction (80%) in C23DO gene expression and a detrimental effect on bacterial populations including key players like Mycobacterium sp., Microbacterium sp., and Thauera sp. involved in the biodegradation of petroleum hydrocarbons.